" تقييم التجربــة الجزائريــة في مجال مكافحـــة جريمـــة تمويـــل الإرهـــاب " (El-Wahat Journal for Research and Studies, 2017)
The problem of the financing of terrorism has imposed a strong shadow on the international community, especially following the events of September 11, 2001, which targeted the United States of America. Since then, international attention has increased to combat this phenomenon, which has caused panic among all societies. Algeria has addressed this phenomenon through a number of measures, In this regard, we will address legal and judicial procedures by promulgating Law No. 05-01 of 06 February 2005 on the prevention and combating of money laundering and the financing of terrorism, which set the legal framework for effective control of this serious crime.The legal experience was assessed through the definition of the crime of financing terrorism, as well as through the legal adaptation of the crime, and then through the elements of this crime. The second axis was the assessment of the Algerian judicial experience. Key words –  Financing of terrorism, legislative control, judicial experience, money laundering